Revealing Attitude and Motivation of Young Efl Learners Through Metaphor Analysis: Learning English in the Crisis Time - Yossy Sunda Permatasari; Sri Rachmajanti; Utari Praba Astuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study aimed to find out learners’ attitude and motivation toward online English learning during COVID-19 outbreak. Eight first graders were involved in an interview session to reveal their perspectives through metaphor. The results of metaphor analysis showed that the learners have low motivation and attitude although they tend to get good score in English subject. Due to many obstacles in its implementation, students, teacher, and parents hope that the English teaching and learning activities can be done face-to-face completely to result in effective learning process.Abstrak: Penelitian ini bertujuan untuk mengetahui sikap dan motivasi siswa terhadap pembelajaran bahasa Inggris online selama wabah COVID-19. Delapan siswa kelas satu dilibatkan dalam sesi wawancara untuk mengungkapkan perspektif mereka melalui metafora. Hasil analisis metafora menunjukkan bahwa siswa memiliki motivasi dan sikap yang rendah meskipun mereka cenderung mendapatkan nilai yang baik dalam mata pelajaran bahasa Inggris. Karena banyak kendala dalam pelaksanaannya, siswa, guru dan orang tua berharap kegiatan belajar mengajar bahasa Inggris dapat dilakukan secara tatap muka sepenuhnya untuk menghasilkan proses pembelajaran yang efektif.